Five adult laryngeal venous malformation cases treated effectively with sclerotherapy. (1st April 2013) - Kamijo, Atsushi; Hatsushika, Kyousuke; Kanemaru, Syuichiro; Moriyama, Motohiro; Kase, Yasuhiro; Masuyama, Keisuke
Abstract : Objectives/Hypothesis: Laryngeal venous malformation is a comparatively rare condition in adults. It presents as a livid or bluish mass that may cause bleeding, hoarseness, stridor, and even difficulty in breathing. So far, treatment has largely consisted of laser therapy and surgical removal. Five cases of adult laryngeal venous malformations that were treated by sclerotherapy (local injection of monoethanolamine oleate solution) are reported. All lesions disappeared after one or two treatment sessions, and two of the five cases that presented recently were cured in the outpatient clinic setting with no sequelae. Sclerotherapy with monoethanolamine oleate is a safe, easy, and effective treatment for laryngeal venous malformations. Level of Evidence: 4. Laryngoscope, 123:2766–2769, 2013